The Role of Microregions in the Regional Development - Hlaváček, Petr (The Role of Microregions in the Regional Development, 2006)
In the article presented the development of the local authorities in the Czech Republic. The author described also microregions and municipality associations. These microregions encourage positive changes for all municipalities and for the country municipalities as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 133-140